No difference in cross-modal attention or sensory discrimination thresholds in autism and matched controls - Haigh, Sarah M.; Heeger, David J.; Heller, Laurie M.; Gupta, Akshat; Dinstein, Ilan; Minshew, Nancy J.; Behrmann, Marlene (Vision research (Oxford), 2016)
Autism has been associated with abnormalities in sensory and attentional processing. Here, we assessed these processes independently in the visual and auditory domains using a visual contrast-discrimination task and an auditory modulation-depth discrimination task. To evaluate changes in sensory function by attention, we measured behavioral performance (discrimination accuracy) when subjects were cued to attend and respond to the same stimulus (frequent valid cue) or cued to attend to one stimulus and respond to the non-cued stimulus (infrequent invalid cue). The stimuli were presented at threshold to ensure equal difficulty across participants and groups. Results from fifteen high-functioning adult individuals with autism and fifteen matched controls revealed no significant differences in visual or auditory discrimination thresholds across groups. Furthermore, attention robustly modulated performance accuracy (performance was better for valid than invalid cues) in both sensory modalities and to an equivalent extent in both groups. In conclusion, when using this well-controlled method, we found no evidence of atypical sensory function or atypical attentional modulation in a group of high functioning individuals with clear autism symptomatology.